2012
DOI: 10.1039/c2lc20949g
|View full text |Cite
|
Sign up to set email alerts
|

Quick genotyping detection of HBV by giant magnetoresistive biochip combined with PCR and line probe assay

Abstract: Genotyping of human hepatitis B virus (HBV) can be used to direct clinically effective therapeutic drug-selection. Herein we report that a quick genotyping method for human HBV was established by a specially designed giant magnetoresistive (GMR) biochip combined with magnetic nanoclusters (MNCs), PCR and line probe assay. Magnetic nanoclusters of around 180 nm in diameter were prepared and modified with streptavidin, and resultant streptavidin-modified magnetic nanoclusters were used for capturing biotin-label… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…Different kinds of ultra-sensitive biosensors have been designed and developed1234567. Chip-based detection of biological agents using giant magnetoresistive (GMR) sensors and magnetic labels have emerged recently8910111213141516, and this GMR sensing technology has the merits of low cost, portability, high sensitivity, and real-time electronic readout. In addition, the fabrication of GMR sensors is compatible with the current large-scale integration technologies, so GMR sensors can be easily integrated and their cost can be greatly reduced as mass production is carried out.…”
mentioning
confidence: 99%
“…Different kinds of ultra-sensitive biosensors have been designed and developed1234567. Chip-based detection of biological agents using giant magnetoresistive (GMR) sensors and magnetic labels have emerged recently8910111213141516, and this GMR sensing technology has the merits of low cost, portability, high sensitivity, and real-time electronic readout. In addition, the fabrication of GMR sensors is compatible with the current large-scale integration technologies, so GMR sensors can be easily integrated and their cost can be greatly reduced as mass production is carried out.…”
mentioning
confidence: 99%
“…Giant magnetoresistive sensors were recently used to genotype the four variants of hepatitis B virus, data that may be of clinical relevance in diagnosis and therapy. 134 The ability of ÎŒTAS platforms to couple diverse functionalities has been well-demonstrated in genotyping applications. An excellent example incorporated continuous-flow PCR amplification, bioaffinity-based sample purification and concentration, and detection by capillary electrophoresis for gender and ethnicity determination of genetic samples.…”
Section: Research Laboratorymentioning
confidence: 99%
“…The authors of [63] recently reported a quick, sensitive genotyping method for human hepatitis B virus (HBV) based on a specially designed GMR biochip, which they combined with magnetic nanoclusters (MNCs), PCR and line probe assay. The GMR multilayers were deposited by DC magnetron sputtering onto Si wafers with a structure of NiFeCo (6 nm)/[Cu (2.2 nm)/NiFeCo (1.5 nm)]10/Ta (100 nm).…”
Section: Microfluidic Biosensing Systems: State Of the Artmentioning
confidence: 99%